Cause-specific excess mortality in siblings of patients co-infected with HIV and hepatitis C virus. - Ann-Brit Eg Hansen; Nicolai Lohse; Jan Gerstoft; Gitte Kronborg; Alex Laursen; Court Pedersen; Henrik Toft Sørensen; Niels Obel (PLoS ONE, 2007)
BACKGROUND: Co-infection with hepatitis C in HIV-infected individuals is associated with 3- to 4-fold higher mortality among these patients' siblings, compared with siblings of mono-infected HIV-patients or population controls. This indicates that risk factors shared by family members partially account for the excess mortality of HIV/HCV-co-infected patients. We aimed to explore the causes of death contributing to the excess sibling mortality. METHODOLOGY AND PRINCIPAL FINDINGS: We retrieved causes of death from the Danish National Registry of Deaths and estimated cause-specific excess mortality rates (EMR) for siblings of HIV/HCV-co-infected individuals (n = 436) and siblings of HIV mono-infected individuals (n = 1837) compared with siblings of population controls (n = 281,221). Siblings of HIV/HCV-co-infected individuals had an all-cause EMR of 3.03 (95% CI, 1.56-4.50) per 1,000 person-years, compared with siblings of matched population controls. Substance abuse-related deaths contributed most to the elevated mortality among siblings [EMR = 2.25 (1.09-3.40)] followed by unnatural deaths [EMR = 0.67 (-0.05-1.39)]. No siblings of HIV/HCV co-infected patients had a liver-related diagnosis as underlying cause of death. Siblings of HIV-mono-infected individuals had an all-cause EMR of 0.60 (0.16-1.05) compared with siblings of controls. This modest excess mortality was due to deaths from an unknown cause [EMR = 0.28 (0.07-0.48)], deaths from substance abuse [EMR = 0.19 (-0.04-0.43)], and unnatural deaths [EMR = 0.18 (-0.06-0.42)]. CONCLUSIONS: HCV co-infection among HIV-infected patients was a strong marker for family-related mortality due to substance abuse and other unnatural causes. To reduce morbidity and mortality in HIV/HCV-co-infected patients, the advances in antiviral treatment of HCV should be accompanied by continued focus on interventions targeted at substance abuse-related risk factors.